2022
DOI: 10.3390/s22134968
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Patient Length of Stay in Australian Emergency Departments Using Data Mining

Abstract: Length of Stay (LOS) is an important performance metric in Australian Emergency Departments (EDs). Recent evidence suggests that an LOS in excess of 4 h may be associated with increased mortality, but despite this, the average LOS continues to remain greater than 4 h in many EDs. Previous studies have found that Data Mining (DM) can be used to help hospitals to manage this metric and there is continued research into identifying factors that cause delays in ED LOS. Despite this, there is still a lack of specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 74 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…Besides the patients requiring other requests, the ones for which consultation was requested had the lowest WT and the highest LOS on average compared to the ones for which laboratory-type or imaging-type tests were ordered ( Table 2 ). Since ordering diagnostic tests or consultation can be related to clinical acuity or complexity of ED patients, 19 , 21 , 32 , 33 these results showed that although patients with higher acuity or complexity levels wait significantly lower in EDs, they stay longer in the system. Additional requests such as diagnostic tests and consultation may cause delays in making decisions on these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the patients requiring other requests, the ones for which consultation was requested had the lowest WT and the highest LOS on average compared to the ones for which laboratory-type or imaging-type tests were ordered ( Table 2 ). Since ordering diagnostic tests or consultation can be related to clinical acuity or complexity of ED patients, 19 , 21 , 32 , 33 these results showed that although patients with higher acuity or complexity levels wait significantly lower in EDs, they stay longer in the system. Additional requests such as diagnostic tests and consultation may cause delays in making decisions on these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors, including sociodemographic, clinical, and hospital-related characteristics, are linked to extended LOS in ED. Previous studies in Australia have shown that factors such as patient age, mode of arrival, triage category, and reason for ED presentations were significantly associated with extended ED LOS [17,18]. However, these studies include all age groups including the elderly population, hence may have missed specific factors associated with extended LOS in ED among the paediatric population -a key focus of this study.…”
Section: Introductionmentioning
confidence: 92%
“…The application of such techniques requires a combination of the technical expertise of computer scientists, as well as domain knowledge to prepare the data sets for analysis and the interpretation of the results. In the sixth article [6], Gurazada, with her colleagues, explored a common problem of a prolonged length of stay in an emergency department. The article presents a review of potential data-mining techniques that have been applied to predict what factors affect the length of stay of patients.…”
Section: Overview Of Contributionmentioning
confidence: 99%